2018
DOI: 10.1111/jpc.13850
|View full text |Cite
|
Sign up to set email alerts
|

Reporting the incidence of unplanned extubation in the neonatal intensive care unit

Abstract: This audit has provided our neonatal intensive care unit with a benchmark for improvement. It has also created staff awareness of the risk of UE and promoted staff engagement to reduce UE. A bundle approach to reduce UE has been introduced. Future audits are planned to monitor the impact of these initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
1
13
0
3
Order By: Relevance
“…2,9,14,15 Our UE rate and identified causes are consistent with other reports in the literature. 2,7,9,10 In our unit, agitation was a commonly cited explanation for UE, followed closely by UE occurring during retaping and with routine handling. Agitation, as noted by the bedside providers, could be the cause of UE or could be the result of an impending UE, and any association between agitation and UE needs to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…2,9,14,15 Our UE rate and identified causes are consistent with other reports in the literature. 2,7,9,10 In our unit, agitation was a commonly cited explanation for UE, followed closely by UE occurring during retaping and with routine handling. Agitation, as noted by the bedside providers, could be the cause of UE or could be the result of an impending UE, and any association between agitation and UE needs to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 87%
“…6,16,17 Some centers have reported more frequent UE during daytime or at change of shift, but we observed no significant difference in UE rates based on time of day in our unit. 10 Given the association of agitation and UE, we evaluated sedation regimens and found that only half of intubated subjects were receiving No CPR: n ϭ 112 subjects; CPR: n ϭ 17 subjects. Data are expressed as median (interquartile range), n (%), or mean Ϯ SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A coleta de sangue, por exemplo, é habitualmente realizada em dois, em que o médico é responsável pelo procedimento de coleta e o auxiliar atua na contenção do paciente. A necessidade de pelo menos dois membros da equipe para realização de procedimentos em recém-nascido intubados é apontada por alguns autores e compõe uma das ações dos bundles de segurança no cuidado destes pacientes 9,10 .…”
Section: Discussionunclassified
“…Sua morbidade, entretanto, não está bem estabelecida e os autores ressaltam a heterogeneidade dos estudos conduzidos sobre o assunto e a baixa documentação do evento, o que dificulta a análise e conhecimento de seu real impacto. O que se sabe, de fato, é que medidas simples de segurança possuem grande eficácia na redução da ENP e devem ser implementadas em UTIN para garantir o melhor cuidado para os recém-nascido em VM [9][10][11]23 .…”
Section: Discussionunclassified